2018
DOI: 10.1111/jocn.14121
|View full text |Cite
|
Sign up to set email alerts
|

Learning lessons from the analysis of patient complaints relating to staff attitudes, behaviour and communication, using the concept of emotional labour

Abstract: An understanding of emotional intelligence can protect staff from burnout and other negative outcomes which those in a caring role can experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 20 publications
(27 reference statements)
4
41
0
Order By: Relevance
“…Providers argued that "An extra person be recruited and given the responsibility to maintain Literature shows that clear quality improvement guidelines and supportive policies enable wellfunctioning patient feedback systems (44). Similar to our results, studies have shown that frontline workers need support to manage feedback effectively and that adequate supervision can help staff value patient feedback (6,43,49,50). However, the mere existence of guidelines is not enough; frontline workers need to be aware of feedback management processes.…”
Section: Processing Feedbacksupporting
confidence: 78%
See 2 more Smart Citations
“…Providers argued that "An extra person be recruited and given the responsibility to maintain Literature shows that clear quality improvement guidelines and supportive policies enable wellfunctioning patient feedback systems (44). Similar to our results, studies have shown that frontline workers need support to manage feedback effectively and that adequate supervision can help staff value patient feedback (6,43,49,50). However, the mere existence of guidelines is not enough; frontline workers need to be aware of feedback management processes.…”
Section: Processing Feedbacksupporting
confidence: 78%
“…Our ndings suggest that while being aware is necessary, mere awareness is not enough for exercising agency and rights, echoing the literature on lack of complaining by the socio-economically disadvantaged in Nepal, Russia and Israel (19,41,42). Fears of retribution and distrust of the system consistently underpin people's decisions to not complain (19,(41)(42)(43)(44)(45). Patients distrust available feedback systems because they doubt the benevolence of the health system and are afraid of retribution.…”
Section: Figure 3 and 4 Heresupporting
confidence: 60%
See 1 more Smart Citation
“…The rich, unstructured narrative within complaints complicates reliable and meaningful extraction of quality and safety insights 16. Various coding taxonomies have been developed to support complaints teams and researchers in codifying complaints reliably 7 9 11 55 65 68–78. To achieve reliable aggregated analysis, the taxonomy should fulfil the following minimum criteria: the categories in the framework are collectively exhaustive, mutually exclusive and reflect patient voice as reported in complaints (ie, validity) 11 79 80.…”
Section: Resultsmentioning
confidence: 99%
“…However, the importance of this work to the success of the medical service system and the provision of high‐quality care cannot be overstated. Nurses inevitably engage in emotional work to promote the well‐being of patients, maintain a harmonious atmosphere in the organisation and maximize safety outcomes (Hogg, Hanley, & Smith, 2018). Based on nurses' professional skills and friendly service attitude, patients develop strong and friendly relationships with nurses and show greater satisfaction with nurses' care (Tajeu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%